Resolute Rebel : General Roswell S. Ripley, Charleston's Gallant Defender - Bennett, Chet (Book collections on Project MUSE., 2017)
The first biography of Gen. Ripley's complex, often contradictory military service in the U.S. and Confederate armies and his postwar British exploits.